Balanced cross-section across the Siwaliks of the Trijuga Valley, eastern Nepal (Journal of Nepal Geological Society, 2020)
The strata of the Siwalik Group in the Trijuga valley is dissected by two thrusts, repeating the succession three times and forming a longitudinal Dun Valley. The total thickness of the Siwalik strata exceeds 5000 m in the area. A balanced cross-section has been constructed across the Siwalik Range in the Trijuga valley showing that the Main Himalayan Thrust (MHT) lies at the depth of about 5.2 km from the surface. The Main Frontal Thrust (MFT), Kamala Tawa Thrust (KTT), Marine Khola Thrust (MKT) and Main Boundary Thrust (MBT) ramp-up from the MHT. Along with these faults, fault-bend anticlines associated with these thrusts have shortened the Siwalik of the area. The shortening across the area has been calculated to be approximately 33.7 km.